PERAN ORGANISASI SANTRI SMA TRENSAINS DALAM MENINGKATKAN MOTIVASI BELAJAR PADA KEGIATAN PENDIDIKAN AGAMA ISLAM STUDI KASUS DI PESANTREN TEBUIRENG 2 JOMBANG - Ahmad Roghib Muri Kurniawan; Imam Bawani (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2022)
Orsatrens (Organization of Santri SMA Trensains) is an intra-school and boarding organization under the auspices of SMA Trensains Tebuireng 2. The focus of this research is (1) The role of the Santri Organization of SMA Trensains (Orsatrens) in increasing learning motivation in Islamic Religious Education (PAI) activities, and ( 2) supporting and inhibiting factors for the role of Islamic boarding schools in increasing learning motivation in PAI activities at Pesantren Tebuireng 2. In this study, researchers used descriptive qualitative research and a case study approach. In analyzing the data, the researcher used several stages, namely data reduction, data presentation, and drawing conclusions. It was found that (1) Orsatren played a role in increasing learning motivation in PAI activities by cultivating and developing the talents and interests of students, especially in leadership, (2) fostering independence and militancy, (3) Orsatren Train how to coordinate, social spirit, good and effective interaction and communication and dare to appear in public, and (4) practice decisions and take responsibility with monitoring and evaluation. Supporting factors for Orsantren activities in increasing learning motivation are (1) the support from organizational advisors (2) support from parents and student local organizational, (3) the emergence of students's motivation to imitate teachers both in schools and cottages, (4) the existence of legitimacy from the lodge about the existence of the santri organization, (5) Adequate facilities. While the inhibiting factors, namely (1) the inactivity of some students in participating in organizational events, (2) the lack of direct assistance by the leadership, (3) it is necessary to increase creativity in holding events that are more desirable, (4) the clash between the dense activities of students in organization and in schools or cottage, and (5) the head of the organization lacks coordination with the central administrators.